Strategi Pembelajaran Mendalam dalam Mengembangkan Kemampuan Membaca dan Menulis Bahasa Indonesia Siswa Sekolah Dasar - Wina Wati (Jurnal Sultra Elementary School, 2025)
This study aims to analyze in-depth learning strategies in developing Indonesian reading and writing skills in elementary school students through a literature study approach. Deep learning emphasizes students' active involvement in critical, reflective, and collaborative thinking processes so that they not only understand texts literally but also interpret their meaning and relate them to real-life contexts. This study was conducted by analyzing 15 selected scientific articles published between 2019 and 2024, relevant to the context of Indonesian language learning in elementary schools. The analysis results indicate that the implementation of in-depth learning strategies has a significant impact on improving student literacy, both in terms of reading comprehension and reflective and argumentative writing skills. Teachers play a crucial role as facilitators, encouraging students to think critically through project-based, problem-based, reflective, and collaborative learning models, as well as the integration of digital technology. These strategies have been proven to support the implementation of the Independent Curriculum, which is oriented towards meaningful learning and strengthening the Pancasila Student Profile. Furthermore, in-depth learning also contributes to increasing learning motivation, curiosity, and the development of reflective, creative, and independent student character. Thus, immersive learning strategies are a relevant and effective approach to strengthening elementary school students' Indonesian reading and writing skills in the 21st-century educational era.